Methane Extraction from Abandoned Mines by Surface Vertical Wells: A Case Study in China - Shengyong Hu; Ao Zhang; Guorui Feng; Xiangqian Guo; Xuyang Miu; Chao Li; Dandan Han; Jin Wang; Lixun Kang (Geofluids)
Considerable methane resources exist in abandoned coal mines. However, methane extraction from abandoned mines in China is still in the exploratory stage. This study presents technologies and engineering practices suitable for the extraction of gob methane from abandoned mines using surface vertical wells, including methane drainage systems, well bottom locations, and an intermittent drainage method. Seven surface wells in the Yongan abandoned mine in China were selected for gob methane extraction. Field results showed that the methane volumetric flow rate of a well whose bottom was close to the gob bottom was 2.5 times greater than that of a well with a bottom located in the gob fractured zone. Moreover, intermittent extraction can enable a well to extract methane cyclically at a high volumetric flow rate. A well drilled mistakenly into a coal pillar can be reused through hydraulic fracturing. The overall maximum methane volumetric flow rate, average concentration, and extraction span were 210 m3/h, 83%, and 1100 days, respectively.